Analysis of Purchase Probability for Reworked Clothing in Implementing SDGs Among Generation Z - Michelle Putri Baswara; Putu Ayu Pramitha Purwanti (International Forum of Researchers and Lecturers, 2025)
Reworked clothing refers to the process of taking existing garments or textiles and transforming them into new clothing. Wearing reworked clothing is one of the best ways to reduce fashion waste while creating unique and environmentally friendly apparel. Generation Z is a digital generation that tends to express themselves through the clothing they wear. This study explains the simultaneous and partial effects of the variables willingness to pay, income, product quality, and conceptual understanding of the SDGs on the purchase probability for reworked clothing. The research was conducted on 100 respondents in South Jakarta who followed the Instagram account @make.them.jealous by distributing an online Google Form questionnaire, with data analysis performed using SPSS software. The purpose of this study was to determine the simultaneous and partial effects of the independent variables on the dependent variable. The results showed that willingness to pay, income, product quality, and conceptual understanding of the SDGs simultaneously had a significant effect on the purchase probability for reworked clothing. However, willingness to pay and income did not have a partial effect on purchase probability for reworked clothing, while product quality and conceptual understanding of the SDGs had a significant partial effect on the purchase probability for reworked clothing.